Effects of Gluten-Free Diet on Quality of Life and Depression in Children With Celiac Disease. Issue 3 (September 2015) - Simsek, Seref; Baysoy, Gokhan; Gencoglan, Salih; Uluca, Unal
ABSTRACT: Objectives: The aim of this study was to investigate the level of depression and quality of life in children with celiac disease (CD). In addition, it aimed to examine the relations of depression level and life quality with adherence to a gluten-free diet (GFD). Methods: Twenty-five children with CD and 25 healthy controls were included. The Depression Scale for Children and the General Purpose Health-Related Quality of Life Scale for Children were performed on patients before and after receiving recommendations to follow a GFD. Results: No significant differences were found in the depression scores between the patients and the control subjects ( P  > 0.05). In contrast, total scores and scores of the emotional well-being subscale of the measure of Quality of Life Scale for Children were significantly lower in patients with CD compared with the control group ( P  < 0.05). No significant improvements were observed in depression or life quality scores of the total subsample of celiac patients, all of whom received a recommendation to follow a GFD ( P  > 0.05). Significant decrease was observed in the depression scores, however, of celiac patients who were able to actually adhere to the GFD compared with nonadherent patients. Conclusions: CD negatively affected quality of life in children. Adherence to GFD was associated with reduction in depression symptoms. Improving the adherence of celiac patients to a GFD may have a favorable effect on their depression symptoms.